In situ TEM study of reversible and irreversible electroforming in Pt/Ti:NiO/Pt heterostructures. Issue 5 (14th April 2015) - D'Aquila, Kenneth; Liu, Yuzi; Iddir, Hakim; Petford‐Long, Amanda K.
<x xml:space="preserve">Abstract</x> Experimental verification of the microscopic origin of resistance switching in metal/oxide/metal heterostructures is needed for applications in non‐volatile memory and neuromorphic computing. Numerous reports suggest that resistance switching in NiO is caused by local reduction of the oxide layer into nanoscale conducting filaments, but few reports have shown experimental evidence correlating electroforming with site‐specific changes in composition. We have investigated the mechanisms of reversible and irreversible electroforming in 250–500 nm wide pillars patterned from a single Ta/Ti/Pt/Ti‐doped NiO/Pt/Ta heterostructure and have shown that these can coexist within a single sample. We performed in situ transmission electron microscopy (TEM) electroform‐ ing and switching on each pillar to correlate the local electron transport behavior with microstructure and composition in each pillar. DFT calculations fitted to electron energy loss spectroscopy data showed that the Ti‐doped NiO layer is partially reduced after reversible electroforming, with the formation of oxygen vacancies ordered into lines in the 〈110〉 direction. However, under the same probing conditions, adjacent pillars show irreversible electroforming caused by electromigration of metallic Ta to form a single bridge across the oxide layer. We propose that the different electroforming behaviors are related to microstructural variations across the sample and may lead to switching variability. (© 2015 WILEY‐VCH Verlag GmbH &Co. KGaA, Weinheim)